Surgical Infections Some Facts - Mohammad Baddour, Manal (IntechOpen, 2020)
Skin is a natural barrier to infection. Surgical breakage of skin can lead to surgical site infections (SSIs). SSIs are relatively common and constitute a problematic issue in surgical procedures. Most common organisms include Gram-positive, such as Staphylococcus and Streptococcus, as well as Gram-negative, such as Pseudomonas and others, bacteria. The extent and outcome of SSI can vary widely depending on the procedure, organism, extent, and other factors, and can result in discomfort, severe morbidity, or even life-threatening conditions.It is thus mandatory to be aware of and follow WHO and CDC guidelines for the prevention of SSIs and to reduce risk factors for acquisition. This book sheds light on certain aspects related to SSIs and how to avoid them.